Kecemasan dan Depresi Dalam Perspektif Al Qur’an - Farida Yuliantari Al Maesyuro, Siti (Lembaga Pendidikan Tinggi Nahdlatul Ulama (LPT NU) PCNU Kabupaten Nganjuk, 2025)
This study analyzes anxiety and depression from the perspective of the Qur’an by exploring their causes and the solutions it offers for achieving psychological well-being. Anxiety and depression are mental and emotional disturbances that arise due to the inability to manage life’s pressures and spiritual instability. This research aims to identify the Qur’anic concept of anxiety and depression and to describe Qur’anic approaches to overcome them. Using a qualitative method with a library research approach, data were collected from classical and contemporary tafsir, psychological studies, and relevant scholarly works. The findings reveal that anxiety (khauf) and depression (huzn) are inherent emotional states of human beings that become harmful when excessive or uncontrolled. The Qur’an provides spiritual and behavioral prescriptions such as dhikr (remembrance of God), prayer, patience, effort, and tawakkul (trust in God) as therapeutic principles to restore emotional balance and mental peace. These practices cultivate optimism, strengthen faith, and reduce negative emotions, demonstrating that the Qur’an offers a holistic framework for mental health grounded in spiritual resilience